Open Surgical Repair of Adult Inguinal and Femoral Hernias: Contemporary Techniques and Clinical Outcomes - Subhan , Nanda (Journal of Society Medicine, 2026)
Groin hernias, particularly inguinal and femoral hernias, represent one of the most common conditions requiring surgical intervention in general surgery. Although minimally invasive approaches have gained increasing popularity, open surgical repair continues to play an essential role in contemporary practice, especially in patients with anatomical complexity, prior pelvic surgery, or contraindications to laparoscopic procedures. This review provides a comprehensive overview of the principles, anatomical considerations, indications, and operative techniques associated with open repair of adult inguinal and femoral hernias. A detailed understanding of groin anatomy, including the inguinal canal, Hesselbach’s triangle, and femoral ring, is fundamental to achieving an accurate diagnosis and ensuring safe surgical repair. Multiple operative techniques have been developed and can broadly be classified into mesh-based tension-free repairs and primary tissue repairs. Among mesh techniques, the Lichtenstein repair remains the most widely adopted approach owing to its technical simplicity, reproducibility, and consistently low recurrence rates. Open preperitoneal mesh repairs also provide effective coverage of the myopectineal orifice and may be particularly advantageous in femoral hernias. Non-mesh techniques, such as the Shouldice, Bassini, and McVay repairs, remain relevant in selected clinical scenarios, particularly when prosthetic material is contraindicated. Overall, open surgical repair remains a safe and effective strategy for the management of groin hernias, offering durable outcomes when performed with meticulous attention to anatomical landmarks and operative techniques. Appropriate patient selection and adherence to evidence-based surgical principles are critical for minimizing complications and reducing recurrence. This review aims to summarize current surgical principles, operative techniques, and clinical outcomes associated with open repair of inguinal and femoral hernias in adult patients.